2021
DOI: 10.21037/gs-21-697
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of factors influencing postoperative drainage time in breast cancer

Abstract: Background: To investigate the related factors affecting the postoperative indwelling time of drainage tubes (hereinafter referred to as drainage time) in breast cancer (BC) and evaluate the effect of pseudomonas aeruginosa-mannose-sensitive hemagglutinin (PA-MSHA) preparation on reducing postoperative drainage time. Methods:The clinical data of 165 BC patients in our hospital, including the postoperative drainage time and occurrence of seroma and related complications (such as fever, incision infection, and f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…Inoue et al ( 27 ) found that patients with BMI had a higher total drainage volume and longer time of drainage. Long et al ( 28 ) reported a positive correlation between BMI and time of drainage and total drainage volume, and Lee et al ( 11 ) also reported a significant positive correlation between BMI and drainage time. These above results are supported by that of the present study which identified that higher BMI was significantly associated with higher total drainage volume and longer time of drainage.…”
Section: Discussionmentioning
confidence: 97%
“…Inoue et al ( 27 ) found that patients with BMI had a higher total drainage volume and longer time of drainage. Long et al ( 28 ) reported a positive correlation between BMI and time of drainage and total drainage volume, and Lee et al ( 11 ) also reported a significant positive correlation between BMI and drainage time. These above results are supported by that of the present study which identified that higher BMI was significantly associated with higher total drainage volume and longer time of drainage.…”
Section: Discussionmentioning
confidence: 97%
“…Postoperative incision infection is a significant cause of failure in patients undergoing breast reconstruction with the implantation of flaps and prostheses. [ 6 ] Both the flap and the prosthesis are alloplastic implants that require a longer time to integrate with tissues, resulting in a longer duration of drainage tube placement compared to simple implantation procedures. [ 7 ] Frequent opening of the drain bottle increases the risk of retrograde infections.…”
Section: Nursing Interventionsmentioning
confidence: 99%
“…Proper management of the drainage tube has been demonstrated to be crucial in preventing the formation of hematoma and infections. [ 6 ]…”
Section: Nursing Interventionsmentioning
confidence: 99%
“…Several in vitro and in vivo studies have shown that Pseudomonas aeruginosa-mannose-sensitive hemagglutinin (PA-MSHA), a genetically modified and inactivated form of Pseudomonas aeruginosa with mannose-sensitive hemagglutinin, can play an anti-tumor role by promoting cancer cell apoptosis, inhibiting cancer cell proliferation, and activating immune cells and cytotoxic effects ( 13 , 14 ). In addition to its antitumor effects, PA-MSHA has been shown in several studies to treat lymphatic leakage in radical mastectomy ( 15 ), gynecologic malignant tumor surgery ( 16 ) and radical thyroidectomy ( 17 ). Lymphatic leakage is also a common complication after PLND, which may affect the postoperative recovery of patients ( 18 ).…”
Section: Introductionmentioning
confidence: 99%